Penentuan Jumlah dan Lokasi Gudang Yang Optimal Dengan Menggunakan Metode Cluster - Sulistyaningsih Jati Murti; Azizah Aisyati; Bambang Suhardi (Performa: Media Ilmiah Teknik Industri, 2004)
This paper proposes Cluster method to determine warehouse number and location of CV. Lidah Buaya Detergent Cream. This Cluster method consist of two algorithms. The fist is used to determine the number of warehouse and the second is used to determine potential warehouse location. On the first algorithm, calculation of total logistic costs is started with warehouses placement at every market area. The number of warehouse reduced one by one, so will be found market area grouping based on proximate distance. The number of optimal warehouse obtained from the calculation of minimum total logistic costs. Potential warehouse location calculated by using central of gravity.